2003
DOI: 10.1037/0012-1649.39.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relations between children's exposure to TV violence and their aggressive and violent behavior in young adulthood: 1977-1992.

Abstract: Although the relation between TV-violence viewing and aggression in childhood has been clearly demonstrated, only a few studies have examined this relation from childhood to adulthood, and these studies of children growing up in the 1960s reported significant relations only for boys. The current study examines the longitudinal relations between TV-violence viewing at ages 6 to 10 and adult aggressive behavior about 15 years later for a sample growing up in the 1970s and 1980s. Follow-up archival data (N = 450)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

27
558
4
31

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 750 publications
(630 citation statements)
references
References 55 publications
(80 reference statements)
27
558
4
31
Order By: Relevance
“…It complements earlier studies conducted with younger children [Anderson et al, 2007;Huesmann et al, 2003] by showing that for adolescents the use of violent electronic games also has a long-term effect on aggressive behavior in the form of physical aggression. There is no indication in the present data that the effects transfer to indirect/relational aggression, which is not commonly addressed by the contents of the games.…”
Section: Discussionsupporting
confidence: 74%
“…It complements earlier studies conducted with younger children [Anderson et al, 2007;Huesmann et al, 2003] by showing that for adolescents the use of violent electronic games also has a long-term effect on aggressive behavior in the form of physical aggression. There is no indication in the present data that the effects transfer to indirect/relational aggression, which is not commonly addressed by the contents of the games.…”
Section: Discussionsupporting
confidence: 74%
“…Youth in the highest quartile of risk on a factor received a 1 indicating "risk present" and those in the lower three quartiles of risk received a 0 indicating "risk absent." The use of upper quartiles for determining the presence of risk ensures a high level of risk and is consistent with prior research conducted by established investigators working within this tradition (e.g., Appleyard et al 2005;Evans 2003;Gutman et al 2003;Huesmann et al 2003). These dichotomized scores were then used to create three new composites.…”
supporting
confidence: 70%
“…However, there now are a few well-conducted studies demonstrating these effects. For example, in a cohort of individuals first assessed during middle childhood and then again in early adulthood, Huesmann et al (2003) found that even after controlling parental SES, children's academic skills, and childhood aggression, childhood TV violence viewing significantly predicted adolescent and adult aggression. Similar findings were reported by Eron et al (1972), Huesmann (1986), Viemero (1996), and Christakis and Zimmerman (2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These features may also favor participants' identification with the game character (Persky & Blascovich, 2006), which in turn has also been associated with increases on aggression (e.g., Huesmann, Moise, Podolski, & Eron, 2003). Wiederhold and colleagues (2003) have also found that immersiveness and realism were highly correlated with two physiological indices (heart rate and skin resistance), and recommended these physiological parameters as objective measures of immersiveness.…”
mentioning
confidence: 99%